HYPERTENSION IN HIGH SCHOOL STUDENTS: GENETIC AND ENVIRONMENTAL FACTORS (HYGEF STUDY). (June 2018) - Fontana, S.; Lanzani, C.; Bigazzi, R.; Zagato, L.; Messaggio, E.; Santini, G.; Nistri, F.; Delli Carpini, S.; Citterio, L.; Simonini, M.; Brioni, E.; Magnaghi, C.; et al.
Abstract : Objective: To evaluate the impact of gene pathways (ADDs, Endogenous Ouabain genetic polymorphisms) in the transition from normotension to hypertension HT we perform a large epidemiological study in 3 regions of Italy (Milan, Mi, Lombardy, Livorno, Li, Tuscani, and Grottaglie, Gt, Puglia) among young (age < 18) high school students. Design and method: During two consecutive medical visits, we collected the anthropometric data and blood pressure values and a spot urine, saliva sample was taken for the DNA study. Results: Preliminary results obtained on 2, 635 boys (f 1, 501, m 1, 134, age 16, 80 ± 1, 83 years) show a regional difference both for estimated urinary Na+ (Li 171.5 ± 2.1, Mi 178.7 ± 2.8, Pt. 196.4 ± 2.5 mEq/24 h, p < 0.001), although SBP values were higher in Tuscany (Li 121.1 ± 0.36, vs Mi 118.9 ± 0.4, Gt 118.4 ± 0.41 mmHg). SBP throughout the sample was significantly correlated with BMI (r = 0.324, p < 0.0001), and with Ur.Na+ (r = 0.138, p < 0.0001). In the analysis of the genotypes, removed environmental factors, the Lanosterol Synthasi (LSS) polymorphism, the enzyme involved in the synthesis of Endogenous Ouabain (EO) and cholesterol, was associated with increased DBP values (LSS AA 69.2 ± 0, 67, LSS AC 68.3 ± 0.32, LSS CC 66.7 ± 0.3 mmHG, p < 0.0001). Carriers of both mutated variants of ADD1 and ADD2 (ADD1GT / ADD2 CT, n = 167) showed greater (p = 0.015) urinary excretion (192.9 ± 4.26 mEq / 24 h) than subjects with genetic variants ADD1 GG / ADD2 CC (n = 826) (185.2 ± 1.9 mEq / 24 h). The Na/K urinary ratio was increased in the boys carrying LSS AA/CYP1A1 CC 4.04 ± 0.41 vs. LSS GG/CYP1A1 AA 3.19 ± 0.35 mEq / L, suggesting an interaction between EO and aldosterone. Conclusions: The results obtained in this young population confirm the role of the Adducin-EO genetic network and allow to identify interactions between environmental factors (different eating habits) and the genetic polymorphisms linked to hypertension. RF-funded study: PE-2011-02346988